2005
DOI: 10.1542/peds.2004-1959
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Among Adolescents: A Review of the Diagnosis, Treatment, and Clinical Implications

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is the most common mental disorder in childhood, and primary care clinicians provide a major component of the care for children with ADHD. However, because of limited available evidence, the American Academy of Pediatrics guidelines did not include adolescents and young adults. Contrary to previous beliefs, it has become clear that, in most cases, ADHD does not resolve once children enter puberty. This article reviews the current evidence about the diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
254
2
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(285 citation statements)
references
References 115 publications
9
254
2
14
Order By: Relevance
“…We found that the CPRS-ADHD index (which measures hyperactivity, impulsivity and inattention) was not associated with age. This is in agreement with the notion that, although hyperactivity may be less evident when children with ADHD grow up, 49 they may still present with impairing ADHD symptoms. However, as we evaluated a sample of adolescent subjects, we cannot exclude that age would have been significantly associated with ADHD symptoms in a sample including younger children.…”
Section: Adhd and Bulimic Symptoms In Obese Children S Cortese Et Alsupporting
confidence: 92%
“…We found that the CPRS-ADHD index (which measures hyperactivity, impulsivity and inattention) was not associated with age. This is in agreement with the notion that, although hyperactivity may be less evident when children with ADHD grow up, 49 they may still present with impairing ADHD symptoms. However, as we evaluated a sample of adolescent subjects, we cannot exclude that age would have been significantly associated with ADHD symptoms in a sample including younger children.…”
Section: Adhd and Bulimic Symptoms In Obese Children S Cortese Et Alsupporting
confidence: 92%
“…Goodman 2007;Hechtman et al 1984;Secnik et al 2005;Weiss et al 1985;Wolraich et al 2005;Young et al 2003).…”
Section: Socio-demographicsunclassified
“…Studies of adults with ADHD have also found higher rates of alcohol and drug use and problems when compared with control samples (Brassett-Harknett and Butler 2007;Goodman 2007;Kessler et al 2006;Secnik et al 2005;Wolraich et al 2005;Young et al 2003). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most adolescents with ADHD display a history of problems with self-regulation, self-initiation, decision-making, time management, and organization (Wolraich et al, 2005), it is common for parents to feel that new freedoms will lead to imminent negative consequences. A natural reaction to this feeling is the assertion of developmentally inappropriate levels of control or assistance (Sibley, Campez et al, 2016).…”
Section: Parenting An Adolescent With Adhdmentioning
confidence: 99%